Pengembangan Aplikasi Portal Penyewaan Barang di Kota Malang Berbasis Web - Fatimah Az Zahra; Fajar Pradana; Eriq Muh. Adams Jonemaro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In various activities, people need goods which don't have to be purchased but can be fulfilled by renting. But the lack of information about rental services, makes renter have to do research to find the proper options of rental service according to their references. Besides that, the process of renting and recording orders by manually or bookkeeping could causes several problems. As a result, determining the rental schedule is difficult, slow in accessing data leases, moreover could make the data to be lost. Web portal is able to integrate and support the specific types of applications such as e-commerce. This easiness helps the services to user become more efficient. By combining the concept of web portal with the business process of rental services, the RentPal application was developed as a platform to bridge the rental services with renter. A filter function will be added to the renter by giving a rating based on the goods that return well and on time. This is intended as a preventive action to reduce fraud committed by tenants. Software development of RentPal using a prototyping design model and has been tested with unit testing, integration testing and validation testing which produces 100% valid for 60 test cases, and usability testing which produces a value of 79% and Cronbach's alpha value of 0,9 (excellent).